Sustainable Marketing Approach to Enhance Tourist Revisit Intention: A Conceptual Study of Island Tourism - Ridho Rafqi, Ilhamalimy; Usep, Suhud; Setyo Ferry, Wibowo (INTI International University, 2025)
Tourism destinations today face growing pressure to balance economic development with sustainability, making it essential for marketing strategies to not only attract travelers but also encourage responsible behavior and return visits. This conceptual paper investigates what influences tourists' intentions to revisit Lombok Island, Indonesia, through the lens of sustainable marketing. The proposed model is based on three key destination attributes attractiveness, accessibility, and amenities and examines how these elements affect tourist happiness, satisfaction, and previous experiences, all of which shape the likelihood of a return visit. The framework posits that a fulfilling travel experience extends beyond the trip itself, contributing to sustainable tourism when visitors are inspired to come back and recommend the location, thereby cutting down on the cost of acquiring new tourists. Tourist happiness encompasses the emotional impact derived from natural beauty, cultural richness, and genuine experiences, whereas satisfaction is based on a rational assessment of service quality and facilities. Previous experiences serve as a built-up memory that fosters lasting loyalty to the destination. In the context of sustainable marketing, the model emphasizes the importance for destination managers and policymakers to invest in eco-friendly infrastructure, community-driven services, and culturally respectful promotions to build long-term value. By aligning tourist well-being with sustainability goals, this study argues that the intention to revisit is both a behavioral result and a key measure of marketing success. In conclusion, the framework stresses that sustainable marketing in island tourism involves more than just drawing visitors it requires aligning their satisfaction with efforts to protect cultural heritage and natural environments, ensuring that Lombok remains a strong and sustainable destination.